2020
DOI: 10.1016/j.envpol.2019.113426
|View full text |Cite
|
Sign up to set email alerts
|

Home environmental and lifestyle factors associated with asthma, rhinitis and wheeze in children in Beijing, China

Abstract: Background:The prevalence of asthma and allergic diseases has increased rapidly in urban China since 2000. There has been limited study of associations between home environmental and lifestyle factors with asthma and symptoms of allergic disease in China. Methods:In a cross-sectional analysis of 2,214 children in Beijing, we applied a two-step hybrid Least Absolute Shrinkage and Selection Operator (LASSO) algorithm to identify environmental and lifestyle-related factors associated with asthma, rhinitis and whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 84 publications
0
39
0
1
Order By: Relevance
“…Parental smoking appears to be a controversial risk factor for allergic rhinitis. Two studies [ 3 , 24 ] showed that maternal smoking is a risk factor for allergic rhinitis. However, the associations between the parental smoking indexes during early childhood and both DDR and current rhinitis in this study were not significant and weak in most cases in terms of aORs even after adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental smoking appears to be a controversial risk factor for allergic rhinitis. Two studies [ 3 , 24 ] showed that maternal smoking is a risk factor for allergic rhinitis. However, the associations between the parental smoking indexes during early childhood and both DDR and current rhinitis in this study were not significant and weak in most cases in terms of aORs even after adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are highly observable socioeconomic and health burdens associated with asthmas and other allergies on the population of Asia, very few investigations have concentrated on these conditions. Studies conducted in China mainly concerned the association between children’s allergic diseases and the home environmental and lifestyle-related factors [ 3 ]; however, few focused on the perinatal period, defined as the stage of child development beginning from the start of pregnancy to the end of the child’s first year of life.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the relationship between ambient indoor environments and child health, the survey in Chongqing was first conducted in 2010 46 (named Phase I hereafter). Increasing urbanization and industrialization, coupled with changes in climate and improved building energy efficiency, have changed lifestyles and indoor environments, which may be associated with the incidence of children respiratory diseases and asthma 8,48,49 . Under such circumstances, the survey was repeated in Chongqing in 2019 (named Phase II hereafter), nearly 10 years after Phase I.…”
Section: Methodsmentioning
confidence: 99%
“…Maternal lifestyle has been reported that it was closely related with offspring's behavior and cardiometabolic health (6)(7)(8). Large population-based study and prospective cohort study both showed that maternal current lifestyle, such as body weight, smoking, and alcohol drinking, had a strong independent correlation with offspring weight status and blood pressure (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%